Conjugated Polymer Chains Confined in Vertical Nanocylinders of a Block‐Copolymer Film: Preparation, Characterization, and Optoelectronic Function. Issue 6 (15th January 2013) - Dong, Ban Xuan; Honmou, Yoshihiro; Komiyama, Hideaki; Furumaki, Shu; Iyoda, Tomokazu; Vacha, Martin
Abstract Hybrid materials composed of phase‐separated block copolymer films and conjugated polymers of the phenylenevinylene family (PPV) are prepared. The PPV chains are embedded in vertical cylinders of nanometer diameter in the block‐copolymer films. The cylinders span continuously the whole film thickness of 70 nm. Incorporation of the PPV chains into the one‐dimensional cylinders leads to modified photoluminescence spectra and to large absorption anisotropy. The hybrid films show electroluminescence from the PPV chains in a simple light‐emitting device at minute doping concentrations, and also exhibit a factor of 19 increase in electron transport efficiency along the single PPV chains.